Reduced injury prevalence in soccer athletes following GPS guided acclimatization - Bertschy, M.; Howard, J.; Oyama, S.; Cheever, K. (International Journal of Exercise Science, 2021)
GPS technology has been used to retrospectively correlate injury risk to changes in training load, however the use of GPS technology to plan and monitor training load over an acclimatization period to prevent musculoskeletal injury remains unexplored. This article reports the utility of GPS technology to help develop and monitor incremental increases in training load while transitioning from off-season to in season to reduce musculoskeletal injury. A series of daily minimum standards were established based on observed training loads in year 1 to gradually acclimate soccer athletes over a 5-week period prior to competition season in year 2. Daily check-ins with GPS data were used to ensure athletes met the standards to safely reach the expected training load of a competitive season. Following the 5-week GPS guided training program a lower overall prevalence of injury (Year 1: 92.6% (95%CI = 75.7-100) vs. Year 2: 55.2% (95%CI = 35.7-73.6)) (p = .002) and overall injury rate (Year 1: 8.1/1000 exposure hours (95%CI = 5.2-12) vs 4.6/1000 exposure hours (95%CI = 2.7-7.5) in year 2 (p = .08)) was observed. The observed reduction in injury prevalence and incidence demonstrates how GPS data can be used to proactively design and monitor preventative chronic training load acclimatization programs.